Depiction of dikpala Ishana with his vahana - Temples of India Project Team (Jio Institute, 2024)
On the northeast corner of the Harshnath Temple wall, dikpala Ishana is depicted with his vahana, a bull. A dwarf figure feeding the bull from a vessel is an interesting feature of the image. A dwarf figure feeding the bull from a vessel is an interesting feature of the image.